Alterations of Serum Magnesium Concentration in Animal Models of Seizures and Epilepsy—The Effects of Treatment with a GPR39 Agonist and Knockout of the Gpr39 Gene - Doboszewska, Urszula; Sawicki, Jan; Sajnóg, Adam; Szopa, Aleksandra; Serefko, Anna; Socała, Katarzyna; Pieróg, Mateusz; Nieoczym, Dorota; Mlyniec, Katarzyna; Nowak, Gabriel; Barałkiewicz, Danuta; Sowa, Ireneusz; et al. (Cells (Basel, Switzerland), 2022)
Several ligands have been proposed for the GPR39 receptor, including the element zinc. The relationship between GPR39 and magnesium homeostasis has not yet been examined, nor has such a relationship in the context of seizures/epilepsy. We used samples from mice that were treated with an agonist of the GPR39 receptor (TC-G 1008) and underwent acute seizures (maximal electroshock (MES)- or 6-hertz-induced seizures) or a chronic, pentylenetetrazole (PTZ)-induced kindling model of epilepsy. MES seizures and PTZ kindling, unlike 6 Hz seizures, increased serum magnesium concentration. In turn, Gpr39-KO mice that underwent PTZ kindling displayed decreased concentrations of this element in serum, compared to WT mice subjected to this procedure. However, the levels of expression of TRPM7 and SlC41A1 proteins—which are responsible for magnesium transport into and out of cells, respectively—did not differ in the hippocampus between Gpr39-KO and WT mice. Furthermore, laser ablation inductively coupled plasma mass spectrometry applied to hippocampal slices did not reveal differences in magnesium levels between the groups. These data show the relationship between magnesium homeostasis and certain types of acute or chronic seizures (MES seizures or PTZ kindling, respectively), but do not explicitly support the role of GPR39 in mediating magnesium balance in the hippocampus in the latter model. However, decreased expression of TRPM7 and increased expression of SLC41A1—which were observed in the hippocampi of Gpr39-KO mice treated with TC-G 1008, in comparison to WT mice that received the same treatment—implicitly support the link between GPR39 and hippocampal magnesium homeostasis.